Front Cover: Iron and Silver Complexes of 4‐(Imidazol‐1‐yl)‐2, 6‐di(pyrazol‐1‐yl)‐pyridine (L), Including a [Fe3(µ‐F)2F6L8]+ Assembly (Eur. J. Inorg. Chem. 46/2020). Issue 46 (11th November 2020) - Capel Berdiell, Izar; Kulmaczewski, Rafal; Warriner, Stuart L.; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract : The Front Cover shows one of the Norber Erratics, a large field of glacial boulders on a high moor in the Yorkshire Dales. The image also contains a linear, trinuclear iron(III)/fluoro assembly which is supported by a potentially ditopic heterocyclic ligand coordinated in monodentate fashion. The new ligand, 4‐(imidazol‐1‐yl)‐2, 6‐di(pyrazol‐1‐yl)pyridine, has divergent tridentate and monodentate metal‐binding domains. Complexes of metal ions bound to one, the other or both of these donor sites are described. More information can be found in the Full Paper by M. A. Halcrow et al.